Forward and Inverse Kinematic of a Manipulator Simulator Software Using Unity Engine - Khoswanto, Handry; Sugiharto, Kevin Nathanael; Sandjaja, Iwan Njoto; Thiang, Thiang (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
Robot manipulator is a technology that is widely used in various applications. Because of the widespread use of robot manipulators, students of Electrical Engineering need to learn about robotics. However, we faced problems that are the price of the robot is relatively expensive and lack of tools to help students for solving mathematical calculations in robotics. The aim of this research is to develop application software for solving the problems that we faced. By using this application software, students can learn about robotics more effective. The application was designed using Unity engine and C# language. The application simulates the movement of robot manipulator either using forward or inverse kinematic equation. The manipulators are limited to 2 and 3 degree of freedoms (DOF). A similar application, RoboAnalyzer, is used for comparing the results of the designed application software. The application has been tested and the results show that mathematical calculation done by the application is approximately same as the result of calculation using mathematic equation. The simulator can simulate the movement of the robot well enough. However, the inverse kinematic calculation can only output one result of all possible results that are resulted by the RoboAnalyzer application.